The Effect of Music on Fetus Movement During Non-Stress Test - Batoul Khodakarami; Marzieh Janesari Ladani; Farideh Kazemi; Soudabeh Aghababaei (Hamadan University of Medical Sciences, 2020)
Introduction: To reduce mortality occurrence on the day of birth, it is recommended to evaluate the health of the fetus during pregnancy. The most widely used technique in most centers as the ideal screening for fetal health assessment is non-stress test. Due to the fact that reducing fetal movement is one of the immediate symptoms of fetal death, this study was conducted to determine the effect of music on fetal movement during non-stress test. Methods: This randomized double-blind clinical trial was performed on 160 first-time pregnant women aged 37-40 weeks who had referred to Fatemieh Hospital in Hamadan, Iran, with a complaint of reduced fetal movement in 2019. Individuals were randomly assigned to two control and experimental groups of 80. In the experimental group, 30 minutes of intervention was performed by listening to non-verbal music, but in the control group, no intervention was performed. Data analysis was performed using SPSS 20 and Chi-square test, Mann-Whitney U test and T test. P-value<0.05 was considered significant. Results: In the intervention group, the average difference in the number of fetal movements was more than the control group and this difference was significant. It had a significant decrease in the number of non-reactive tests in the intervention group compared to the control group (P<0.001). The number of basal fetal heart in the intervention group decreased significantly compared to the control group (P=0.01). Conclusion: Music can improve fetal movements and increase the number of reactive tests.